PENGARUH RETURN ON EQUITY DAN RETURN ON INVESTMENT TERHADAP HARGA SAHAM DI MEDIASI INVESTMENT OPPORTUNITY SET: SEKTOR PERTAMBANGAN BATUBARA 2017-2019 - Rohma, Miptaqul; Devy Yulvia Ratna Sary, Clara (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2022)
This study aims to determine the relationship between Return On Equity and Stock Price, the results showed a value of 0.561 with a t-count of 3.325 which is greater than t-table (> 1.96). Shows that Return On Equity has an influence on Stock Prices, which means that the high or low results of the calculation of Return On Equity affect the increase in Stock Prices. Meanwhile, the calculation results of Return On Investment to Investment Opportunity Set is -0.249 with a t-count of 1.883 which is smaller than t-table (<1.96) which means that the amount of Return On Equity does not affect the Investment Opportunity Set. It can be concluded that Return On Equity has an effect on Stock Prices but the Investement Opportunity Set mediating variable cannot affect the independent variables (Return On Equity) and the dependent (Share Price). The next objective is to determine the relationship between Return On Investment and Stock Price -0.308 with a t-count of 1.436 which is lower than t-table (<1.96) which indicates that Return On Investment has a negative effect on Stock Prices. Based on the path coefficient value of the effect of Return On Investment on the Investment Opportunity Set is 0.500 with t-count 3.062 which is higher than t-table (> 1.96), the higher the Return On Investment affects the Investment Opportunity Set, the conclusion is that Return On Investment is not effect on stock prices but affect the mediating variable (Investment Opportunity Set). Investment Opportunity Set affects the independent variable (Return On Investment) and the dependent variable (stock price). Information on the financial performance of coal mining is able to improve positive signals through the Investment Opportunity Set mediating variable, but Return On Equity does not respond positively to investors, investors respond more to financial performance as measured by Return On Investment.